Analisis Pengembangan Arsitektur Enterprise PT Cottonink Duo Kreasindo Pasca Implementasi Sistem ERP SAP Business One dengan Pendekatan TOGAF Framework - Hidayat, Muhammad Imam; Arief, Rifiana (Jurnal Sistem Informasi Bisnis, 2025)
PT Cottonink Duo Kreasindo utilizes SAP Business One technology to assist business operation used production, warehouse, MD Sales and operational as the moduls. In practice, deficiencies are still found that hamper work and operational productivity to improve information system support to improve and complete requirement. To ensure that PT Cottonink Duo Kreasindo require a system that able to facilitate users and run optimally, a paradigm requires function is to plan, design and develop the system; enterprise architecture. Enterprise architecture expectantly able to provide solutions for PT Cottonink Duo Kreasindo to increase the productivity and further align business strategy with the company's information systems. The TOGAF ADM method applied in this research. The blueprint resulting by enterprise architecture planning using the TOGAF ADM method includes detailed architectural designs, including business architecture, data architecture, application architecture, information system architecture, and technology architecture. There are two modules that need to be removed and six modules that need to be added to the business architecture; three modules that need to be removed and two modules that need to be added to the data architecture; as well as four modules that need to be added to application architecture and technology architecture.